Model Penilaian Kinerja Guru Sekolah Dasar Berdasarkan Regulasi dan Nilai-Nilai Islam - Nuridin Nuridin; Ira Alia Maerani (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2022)
This study revealed the performance assessment model of Sultan Agung Islamic Elementary School managed by the Sultan Agung Waqf Foundation (YBWSA). As an Islamic school, the vision based on Islamic values ​​stated in the Quran. This vision also underlies the entire operational process of the school, including the establishment of teacher performance assessments. In addition, teacher performance appraisal refers to the applicable laws and regulations. This research was conducted by implementing a qualitative approach. The informants of the study were the Head of the Secretariat for Primary and Secondary Education, the official assessor for teachers at the Sultan Agung Islamic Elementary School. Data was collected through interviews, observation, and documentation. Meanwhile, the analysis was carried out through a qualitative descriptive, which was intended to obtain an overview of the teacher performance appraisal model of Sultan Agung Islamic Elementary School. The results of the study stated that Sultan Agung Islamic Elementary School had established a trustworthy and professional teacher profile. This profile evaluated through a teacher performance appraisal model based on Islamic regulations and values. The aspects of assessment and indicators are compiled and used as a guidance in assessing teacher performance. The application of assessment model performed effective for the teacher performance appraisal model. ABSTRAK Penelitian ini ingin mengungkap model penilaian kinerja guru Sekolah Dasar Islam Sultan Agung yang dikelola oleh Yayasan Badan Wakaf Sultan Agung (YBWSA). Sebagai sekolah Islam, visi yang ditetapkan mendasarkan pada nilai-nilai Islam yang terdapat dalam Al-Quran. Visi ini pula yang melandasar keseluruhan proses operasional sekolah termasuk dalam melakukan penilaian kinerja guru. Penilaian kinerja guru juga mengacu pada peraturan perundang-undangan yang berlaku. Penelitian ini dilakukan dengan pendekatan kualitatif. Informan dalam penelitian ini adalah Kepala Sekertariat Bidang Pendidikan Dasar dan Menengah, Pejabat penilai guru SD Islam Sultan Agung. Pengumpulan data dilakukan melalui wawancara, observasi, dan dokumentasi. Sedangkan analisis dilakukan melalui deskriptif kualitatif yang dimaksudkan untuk memperoleh gambaran tentang model penilaian kinerja guru SD Islam Sultan Agung. Hasil penelitian menyebutkan, SD Islam Sultan Agung telah menetapkan profil guru amanah dan professional. Profile ini dievaluasi melalui model penilaian kinerja guru yang mendasarkan pada regulasi dan nilai-nilai Islam. Aspek penilaian dan indikator disusun dan dijadikan panduan dalam melakukan penilaian kinerja guru. Model penilaian ini efektif diterapkan sebagai model penilaian kinerja guru.